The Financial Inclussion of The Garut District Society is Analyzed through Financial Literacy and The Use of Fintech - Wufron, Wufron; Susilawati, Wati; Akbari, Rizky Ayu; Hadita, Akmala (Fakultas Ekonomi Universitas Garut, 2023)
The purpose of this research is to investigate how financial inclusion among the residents of Garut is influenced by the use of fintech and financial literacy. The research methodology employs quantitative, descriptive, and verificative techniques, utilizing questionnaire surveys and literature reviews as data collection methods. Partial data analysis is conducted using SPSS and multiple regression analysis. According to the research findings, financial inclusion is positively and significantly influenced by financial literacy. Additionally, the second variable, the use of fintech, also has a positive and significant impact on financial inclusion. A novelty in this study is the exploration of fintech usage in the general community through dimensions such as perspectives, attitudes, intentions, and satisfaction related to financial literacy in financial inclusion. This means that the discussion in this research is not widely covered by previous researchers. The uniqueness lies in the focus on Garut, an area that has not been extensively studied, where the Regional Financial Access Acceleration Team has been established to advance financial literacy and comprehensive implementation of Government Digital Transactions or digitally-based transactions. This research is essential as it relates to the financial conditions of the community, a crucial aspect that, if problematic, can impede well-being.